5: STATUS OF THE INTRODUCED RIO GRANDE TURKEY IN NORTHEASTERN IOWA*† - Dennis D. Wigal (Wildlife Society Bulletin)
ABSTRACT After the extirpation of the eastern wild turkey (Meleagris gallopavo silvestris) in Iowa, several unsuccessful attempts were made to reestablish turkeys in the wild. Then, during the winter of 1960‐61, 39 Rio Grande turkeys (M. g. intermedia) from Texas were introduced in the Yellow River State Forest in Allamakee County, Iowa. The population was studied in three northeastern Iowa counties from June 1966 through September 1967; concentrated field studies were centered in and near the Paint Creek Unit of the forest. Although reproduction has occurred each year since the introduction, poult survival has seemingly been sporadic. Nevertheless, sight records collected through September 1967 show extension of the turkeys' known range every year since the stocking. Verified sightings have been made across the Mississippi River in Wisconsin and up to 41 miles from the release area in Iowa. The turkey population is being suppressed by an unknown factor or factors. Lack of adaptability of Rio Grande turkeys to the northeastern Iowa climate may be a limiting factor. The absence of truly extensive turkey habitat may also limit the population, which appears relatively stable but probably has never exceeded 100.